THE MARKETING COMPETITION AND BUSINESS STRATEGY IN FORMING AND PROTECTING OF THE COMPETITIVE ADVANTAGES OF RAIL PASSENGER TRANSPORT - Melnyk, T. S.; Khrystofor, O. V. (Science and Transport Progress, 2009)
The article is devoted to consideration of basic models of choice of marketing competition and business strategy directed on forming of set of competitive advantages of railway transport, providing and defense of competitively attractive positions at the market of transport services for population. The practical aspects of these problems are represented in the article too.